Complete spontaneous regression of congenital epulis in a baby by 8 months of age - VIVIEN T. SAKAI, MARINELE R. CAMPOS, MARIA APARECIDA A. M. MACHADO, JOSÉ ROBERTO P. LAURIS (IAPD and Blackwell, 2007)
Congenital epulis (congenital granular cell tumour) of the newborn is a rare benign softtissue tumour. It is between eight and 10 times more common in females than in males.